Literature review on micro and macro factors of change in servitization - How could companies facilitate the change towards digital servitization? - Niemelä, Karita Maria (My University, 2020)
Research and literature on servitization have expanded greatly in the past years. This study focuses on providing systematic literature review of the micro and macro factors of change in servitization to find solutions for companies to facilitate the change towards digital servitization. This systematic review classifies equally environmental and organizational qualities from the servitization research and is conducted from descriptive sample of 95 articles covering digital servitization and organizational change. The review results indicate that extensive investments required for digital servitization demand substantial growth of value creation and appropriation. Furthermore, the implementation of digitalization obliges to invest in additional capabilities and resources. There are also various micro and macro level factors that need to be acknowledged and taken into consideration as they may all affect the servitization change process in different ways. To facilitate the digital servitization change process, attention needs to be paid to value creation, planning and analysing, management, capabilities and resources, monitoring, network, and stakeholders with the additional factors concluded in this research. These findings have potential to provide beneficial insights both for the companies in the path of servitization and for the research community by providing a novel literature review with perceptive future research ideas of the field and beyond.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development